Impact of white blood cells on thrombotic risk in patients with optimized platelet count in essential thrombocythemia. (12th June 2018) - Buxhofer‐Ausch, Veronika; Steurer, Michael; Sormann, Siegfried; Schloegl, Ernst; Schimetta, Wolfgang; Gisslinger, Bettina; Schalling, Martin; Krauth, Maria Theresa; Thiele, Jürgen; Ruckser, Reinhard; Gastl, Günther; Gisslinger, Heinz
Abstract: Objectives: Risk of thrombosis is significantly enhanced by both elevated platelet (PLT) and white blood cell (WBC) counts according to a retrospective analysis of a large anagrelide registry in thrombocythemic MPN patients. We were interested in the impact of elevated WBC counts on thrombosis risk in patients where PLT counts were reduced below the calculated cutoff of 574.5 G/L by treatment with anagrelide. Methods: Cox regression analysis and Kaplan‐Meier plot were applied on all patients in the registry with optimized PLT counts. Results: Using the calculated cutoff of 9.66 G/L for WBC, Cox regression analysis revealed a clear influence of elevated WBC counts on the occurrence of a major thrombotic event ( P  = .012). A Kaplan‐Meier plot revealed a markedly shorter time to a major thrombotic event for patients with WBC counts above the cutoff ( P  = .001). Conclusions: These data suggest that additional correction of elevated WBC counts is mandatory in patients with optimally managed PLT counts to reduce thrombotic risk. This study is the first investigation in a prospectively observed large patient cohort which was treated homogenously allowing for evaluation of single parameters for an effect on thrombophilia.